Quality of life of the elderly - Rosenfeld, Lilia (Kultura-Społeczeństwo-Edukacja, 2018)
Drawing on Simone de Beauvoir’s call for a change perspective on old age, as perceive, this article reviews the literature for factors and aspects that influence the quality of life of the elderly. Simone de Beauvoir saw old age as the individual’s unending struggle with the indifference that elderly people encounter, and with pain and illnesses. The improvement in the situation of the elderly cannot be accomplished by merely raising pensions and providing fair housing; rather it is necessary to have a more profound change – a change of life (de Beauvior, 1996). Hence, improving the quality life of elderly people necessitates a more holistic approach, that considers physical functioning, mental, social, environmental and cognitive condition in addition to traditional aspects involving health and economic aspects.